Influenza and Pertussis Vaccine Uptake during Pregnancy: Determinants Found through a Multi-Center Questionnaire Study of Pregnant Women and Healthcare Professionals. Issue 1 (2nd January 2023) - Tsamandouras, Ioannis; Spyromitrou-Xioufi, Panagiota; Matalliotakis, Michail; Matalliotaki, Charoula; Ladomenou, Fani
Abstract: The objective of this article is to assess the adherence of pregnant women to the national recommendations for influenza and pertussis vaccination and the reasons behind their non-adherence. This was a retrospective observational study conducted in a well-defined puerperant population of adequate healthcare standards from December 2018 to December 2019. The study was carried out with 1006 puerperants and 66 health care practitioners. Data were collected, including demographic-obstetric features of pregnant women, whether they received antenatal vaccination, the reasons for having been vaccinated or not as well as health professional's opinion regarding antenatal immunization. The uptake of influenza and pertussis vaccine during pregnancy was suboptimal with lack of recommendation of the vaccine by the healthcare providers being the main barrier. Factors positively associated with antenatal vaccination against influenza were higher level of maternal education and advanced maternal age while antenatal vaccination against pertussis was positively associated with higher level of maternal education. This large-scale retrospective study reveals the inadequacy of antenatal vaccination rates against pertussis and influenza in Crete, Greece. Results suggest that obstetricians' confidence in vaccination is of outmost importance for implementing immunization in pregnancy and any doubts on vaccine effectiveness and safety should be resolved. Routine antenatal vaccination counseling and pregnancy immunization campaigns are essential to improve vaccine uptake during pregnancy.